Physical performance and compensation strategies of older adults to maintain physical fitness and well-being during the COVID-19 pandemic in Germany - Torben Gehle; Sandra Lau; Michel Hackbarth; Tania Zieschang; Jessica Koschate (BMC Geriatrics, 2023)
Abstract Introduction During the first wave of the COVID-19 pandemic in March 2020, worldwide restrictions in social life, including the closure of sport facilities, led to a reduction of physical activity and subjective well-being. The aim of this study is to describe physical training habits, and subjective well-being in relation to objective training data from a chip-controlled fitness circuit in the rural area of Oldenburg, Germany. Materials and methods Overall, 35 older adults (20 women 71 ± 6 y/o and 15 men, 72 ± 7 y/o), regularly exercising in a chip-controlled fitness circuit before the lockdown in March 2020, were interviewed. The training data from February to August 2020 from six strength and two endurance exercise devices were extracted and compared to data before and up to three months after the lockdown. Additionally, participants’ personal characteristics, physical activities and quality of life before, during, and after the first lockdown were assessed. Results The leg score (pre, postJune, postJuly, postAugust: 1207 ± 469 kg, 1248 ± 477 kg, 1254 ± 516 kg, 1283 ± 493 kg; p = 0.137) and endurance scores (ergometer: 0.93 ± 0.35 min− 1 · watt− 1, 0.86 ± 0.31 min− 1 · watt− 1, 0.86 ± 0.31 min− 1 · watt− 1, 0.85 ± 0.28 min− 1 · watt− 1 ; p = 0.442) were not significantly different, in contrast to the rowing score (1426 ± 582 kg, 1558 ± 704 kg, 1630 ± 757 kg, 1680 ± 837 kg; p < 0.001). A significant increase of total energy expenditure (p = 0.026), mainly through gardening, walking, and bike riding was observed. The greatest personal limitation reported, was the loss of social contacts. Conclusion The presented data did not show a decrease in training performance, but a slight trend towards an increase. A compensatory increase in regular outdoor activities seems to have a protective effect against a loss of training performance and may have the potential to stabilize subjective well-being during lockdown periods.